Características epidemiológicas, clínicas e laboratoriais de gatos com sinais de doença do trato urinário inferior - Ferreira, Guadalupe Sampaio [UNESP]; Carvalho, Marileda Bonafim [UNESP]; Avante, Michelle Lopes [UNESP] (My University, 2014)
Feline idiopathic cystitis (FIC) is the most common cause of feline lower urinary tract disease (FLUTD), whereas bacterial cystitis is diagnosed only in 1% to 3% of the cases. The aim of this study was to evaluate cats with presentation or history of lower urinary tract signs disease (LUTSD), considering epidemiological, clinical and laboratory aspects. From March 2011 to October 2012, 45 cats presenting LUTSD and five health cats were evaluated regarding to the history, physical examination, abdominal ultrasonography and laboratorial analyses (CBC, urinalysis, clinical chemistry and urine culture). For the 45 cats presenting LUTSD, the diagnosis included non-obstructive FIC, obstructive FIC, and bacterial cystitis. There were no significant differences in the urine specific gravity, pH and quality of the urine sediment between al FLUTD categories. The hematuria was higher in cats with LUTSD, and piuria was associated mainly to bacterial cystitis. Additionally, other findings suggest that features as breed, age, gender, and neutering were not associated with LUTSD presentation in felines.
Epidemiologic, clinic and laboratorial characteristics of disease cats with lower urinary tract signs
Keywords: Cat; Cystitis; Feline lower urinary tract